A bibliometric analysis of CSR in the banking industry: a decade study based on Scopus scientific mapping. Issue 1 (7th May 2021) - Zainuldin, Mohd Haniff; Lui, Tze Kiat
Abstract : Purpose: This study bibliometrically describes and depicts the intellectual structure and knowledge progress of CSR studies in the banking industry. Design/methodology/approach: Bibliometric analysis is used to quantitatively examine the bibliographic data that gathered from Scopus database. The evaluative and relational techniques are employed to produce the findings and mappings for research themes, impact and directions, as well as collaboration trends. A topical classification is also included to review the results of different types of analysis. Findings: This study discusses how the CSR literature in the banking industry has evolved between 2009 and 2019. The publications increase significantly from 2015 to 2019 and the top journals, authors, affiliations and countries are identified. Stakeholder, disclosure, financial performance, Islamic banks, corporate governance and international banks are among the popular research and collaboration trends found in the extant literature. Reflecting on the arguments in the previous literature, several key research gaps and further suggestions are acknowledged for future studies. Research limitations/implications: The bibliographic data used in this study bounds to Scopus database and the methodology itself suffers a few limitations, which integration of other methodologies will be worthwhile to unearth the field beyond the current discovery. Practical implications: This study is beneficial to potential researchers, scientific journal editors, and bankers to understand the current research progression and evolution within CSR field in the banking sector. Originality/value: Compared to the existing bibliometric literature, this study is among the pioneer wide-ranging bibliometrics study covering co-word, citation, bibliographic coupling, co-authorship and co-citation for CSR research in the banking sector.